Synoptophore in binocular vision anomalies: A short review - Rajesh Kumar; Neebha Passi; Sanjay Kumar Mishra; Manish Kumar Prajapat (Journal of Clinical Ophthalmology and Research)
Binocular vision is a condition in which an individual uses both of their eyes to fixate on an object of regard, resulting in a simultaneous visual perception. Synoptophore is an appropriate orthoptic device to diagnose and treat most strabismic and nonstrabismic binocular vision anomalies. This article aims to provide information on measuring the angle of deviation, cyclofusion, abnormal retinal correspondence, the accommodative convergence/accommodation ratio, pseudotropia, and various anti-suppression exercises on synoptophore. The previous literature lacks detailed information about the synoptophore and its practical applications. This review involved a search on PubMed and Google Scholar using the keywords “synoptophore” and “binocular vision anomalies” followed by an examination of the relevant papers. We shortlisted 20 relevant papers for this review article. We conducted a cross-examination of the cited references and included the most relevant ones.